2022
DOI: 10.1002/ece3.8867
|View full text |Cite
|
Sign up to set email alerts
|

Estimating herbaceous aboveground biomass in Sahelian rangelands using Structure from Motion data collected on the ground and by UAV

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The usefulness of GLI in predicting biomass and green vegetation has been highlighted by previous studies. Taugourdeau et al [ 73 ] found GLI to be among the most important variables when estimating herbaceous above-ground biomass in Sahelian rangelands. In another study, GLI was found to show higher sensitivity in detecting green vegetation [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of GLI in predicting biomass and green vegetation has been highlighted by previous studies. Taugourdeau et al [ 73 ] found GLI to be among the most important variables when estimating herbaceous above-ground biomass in Sahelian rangelands. In another study, GLI was found to show higher sensitivity in detecting green vegetation [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…These data could be used to develop calibrations between field measurements and UAV outputs. One part of the data (the tree from the landscape data set) has already been used to develop calibrations (Bossoukpe, Faye, et al, 2021; Bossoukpe, Ndiaye, et al, 2021; Taugourdeau et al, 2022). One possible interest could be to carry out a meta‐analysis to develop calibrations on a larger scale across different types of vegetation, but also between different UAVs and flight plans.…”
Section: Potential Uses Of Theses Data Setsmentioning
confidence: 99%
“…Schulze-Bruninghoff et al ( 2021) suggested a method combining lidar-derived metrics (sum of voxels, canopy height model, and canopy surface structure) and vegetation spectral properties to estimate fresh and dry biomass in a machine learning approach. In addition, by combining ground camera and UAS, Taugourdeau et al (2022) extracted vegetation metrics from RGB bands and height to estimate aboveground biomass in a random forest model. Therefore, the uncertainty of biomass estimation is limited to the uncertainty in CHM, data resolution, and the type of land treatments (grazed or ungrazed).…”
Section: Introductionmentioning
confidence: 99%